Atopy and asthma in children born to mothers at risk of gestational diabetes mellitus: a follow-up study - Anu Bärenson; Aili Tagoma; Heili Varendi; HEDIMED investigator group; Raivo Uibo (BMC, 2024)
Abstract Background Gestational diabetes mellitus (GDM) is the most prevalent metabolic disturbance during pregnancy and is associated with adverse outcomes in offspring, including an elevated risk for developing atopic diseases in early childhood. Research is limited regarding only women at risk of GDM among whom some develop GDM while others do not. Information about adverse health outcomes in the offspring of these women is also lacking. The main aim was to assess whether maternal GDM increases the offspring's risk of atopic dermatitis (AD), asthma and allergic rhinitis at 1, 2 and 5 years of age. The second aim was to analyze the association of other maternal health characteristics on the development of these disorders in offspring. Methods The follow-up study group of the Gestational Diabetes Study (GDS), conducted at Tartu University Hospital, Estonia, between 2014 and 2020, comprised 223 mother-child dyads. All women had at least one risk factor for GDM, of whom only some developed GDM. Information about the diagnoses of interest was obtained from Electronic Health Records. Allergen-specific IgE from children's serum was measured using ImmunoCAP™ Phadiatop™ Infant, with results ≥ 0.35 kU/l considered positive. Statistical analysis was performed using the RStudio software (version 4.3.0). Results According to our results, only the cases of GDM requiring the use of antidiabetic medications were associated with the development of asthma and/or allergic rhinitis at 2 years of age (aOR 4.68, 95%CI 1.08-20.21, p = 0.039). Maternal obesity (BMI > 30) was associated with offspring´s asthma and/or allergic rhinitis diagnosis at 2 years of age (aOR 3.15, 95%CI 1.03-9.63, p = 0.045). Maternal abnormal weight gain during pregnancy was associated with asthma and/or allergic rhinitis at 5 years of age (aOR 2.76, 95%CI 1.04-7.31, p = 0.041). Conclusion Among pregnant women at risk for GDM, maternal weight-related factors significantly influence the development of atopic diseases in their children between 1 and 5 years of age, regardless of the GDM diagnosis. This suggests that, besides women with GDM greater attention should also be paid to women at risk but who do not develop GDM, as their children seem to be at higher risk of atopic diseases.